Benefits and threats to using social media for presenting and implementing evidence - Cook, C.; O'connell, N.; Hall, Toby; George, S.; Jull, G.; Wright, A.; Girbés, E.; Lewis, J.; Hancock, M. (American Physical Therapy Association, 2018)
As a potential high-yield tool for disseminating information that can reach many people, social media is transforming how clinicians, the public, and policy makers are educated and find new knowledge associated with research-related information. Social media is available to all who access the internet, reducing selected barriers to acquiring original source documents such as journal articles or books and potentially improving implementation-the process of formulating a conclusion and moving on that decision. The use of social media for evidence dissemination/implementation of research has both benefits and threats. It is the aim of this Viewpoint to provide a balanced view of each.